Understanding of the Challenges of the Writing Work in Academia World: What Publication Say - Prasetyono Hendriarto; Muhammad Nur; Asmadianto Asmadianto; Budi Sulistiyo Nugroho (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2021)
This article discussed various types of academic or intellectual papers from academic assignments and projects. Understanding the various writing types in academic work is very important because it serves to communicate the knowledge gained through a series of searches that involve research activities in various disciplines. The researchers have obtained literature related publications, and review them with descriptive design analysis to obtain data findings that answer the topic of discussion. The researchers involve a coding system, in-depth interpretation, and data conclusion taking elements of high validity and reliability of this study's findings. Finally, summarize the findings of this study; this thesis's result can be summed up with some significant pings, among others, that academically speaking, challenges in writing were not new.. The difficulty of writing scholarly was a problem for non-academic students [the English speaker] and other nationalities. For this reason, this analysis merely offers an interpretation of that in a traditional academic language. Keywords: Understanding Academic Writing, Academia Works, Publication Review